In Vivo Hypoglycaemic Effect and Inhibitory Mechanism of the Branch Bark Extract of the Mulberry on STZ-Induced Diabetic Mice - Hua-Yu Liu; Meng Fang; Yu-Qing Zhang (The Scientific World Journal)
Branch bark extract (BBE) derived from the mulberry cultivar Husang 32 (Morus multicaulis L.) with aqueous alcohol solution has been investigated as an inhibitor of α-glycosidase in vitro. Mulberry BBE was orally administered to STZ-induced diabetic mice for three weeks, and it improved the weight gain and ameliorated the swelling of liver and kidney in diabetic mice. Obviously, mulberry BBE not only can reduce the abnormally elevated levels of serum insulin and ameliorate insulin resistance induced by STZ, but also it regulates dyslipidemia in diabetic mice. To understand this therapeutic effect and the regulatory mechanisms of BBE in diabetic mice, a qRT-PCR experiment was performed, indicating that the mulberry BBE can regulate the mRNA expression of glycometabolism genes in diabetic mice, including glucose-6-phosphatase (G6Pase), glucokinase (GCK), and phosphoenolpyruvate carboxykinase (PEPCK), thereby regulating sugar metabolism and reducing the blood glucose level in diabetic mice. The mulberry BBE can increase the mRNA expression of the genes Ins1, Ins2 and pancreatic duodenal homeobox-1 (PDX-1) and may decrease the insulin resistance in diabetic mice. Those results provide an important basis for making the best use of mulberry branch resources and producing biomedical drugs with added value.